P593 Efficacy, tolerance and safety of low-volume bowel preparations in inflammatory bowel diseases: Results from a French national multicentre study. (16th January 2018) - Briot, C; Faure, P; Parmentier, A L; Gay, C; Trang, C; Nachury, M; Viennot, S; Altwegg, R; Bulois, P; Thomassin, L; Serrero, M; Ah Soune, P; et al.
Abstract: Background: Standard high-volume PEG (polyethylene glycol) bowel preparations are usually advised in inflammatory bowel disease (IBD) patients for colonoscopy. Other, low-volume, preparations may be used in clinical practice but very few study have evaluated their safety and tolerance. The aim was to evaluate efficacy, tolerance and safety of the various bowel preparations in IBD, including low-volume preparations. Methods: We conducted a French prospective multicentre observational study, during 1 month. Inclusion criteria were: patients aged 18–75 years, IBD or symptoms of IBD for at least 3 months, indication of colonoscopy independent from the study. The choice of the preparation was left to the investigators as per their usual protocol. Patients, disease and colonoscopy characteristics were recorded by physicians and patients were given self-reported questionnaires. Results: Twenty-five public and private centres in France enrolled 278 patients. Among them, 44 had a disease flare at the time of colonoscopy and 41 had bowel stenosis. 42% received two litres polyethylene glycol with ascorbic acid (PEG 2L), 29% sodium picosulphate (Pico), 15% four litres PEG (PEG 4L) 4L and 14% received sodium phosphate (NaP) or sodium, magnesium and potassium sulphates (MPS). The preparation did not reach the efficacy outcome (Boston score ≥7) in the PEG 4L group in 51.2% of the patients ( p = 0.0011). The preparation intake was complete for 59.5% in the PEG 4L group compared with 82.9% in the PEG 2L group and 93.8% in the Pico group ( p < 0.0001). For all outcomes, tolerance assessed by patients and physicians visual analogue scale was significantly better with both Pico and PEG 2L compared with PEG 4L; and better with Pico compared with PEG 2L ( p = 0.008 and p = 0.0003). Major tolerance endpoints (unpleasant taste, excessive thirst, nausea and vomiting) were significantly altered in the PEG 4L group. Adverse events occurred in 4.3% and were independent from the preparations. Conclusions: Low-volume preparations, including Pico and NaP were actually used by gastroenterologists for IBD patients in France. Preparations with PEG 2L and Pico achieved equally safe preparations, with better efficacy and fare better tolerance compared with high-volume PEG preparations. The best efficacy/tolerance/safety profile was achieved with the Pico preparation. These results need further confirmation by randomised trials.